Consumption of benzodiazepines in the city of Belém-PA: comparative study of the first semester from 2020 to 2022 (Research, Society and Development, 2023)
Benzodiazepines (BZD's) psychoactive drugs that act as allosteric modulators (agonists) of the type A γ-aminobutyric acid (GABA-A) receptor in the central nervous system. In clinical practice, these drugs are often used and prescribed in the treatment of anxiety, insomnia and depression. Due to its various pharmacological actions, and prolonged use, it makes it among the five best-selling drugs in Brazil. The lack of information about the consequences of irrational use increases vulnerability to generating dependence. Therefore, this study sought to analyze the consumption and distribution of BZD’s in the city of Belém - Pará. An observational, longitudinal, and retrospective survey was used in this study, comparing the first half of the years 2020 to 2022, through the SNGPC system. The variables analyzed were amount of BZD’s per year, age group, sex and type of drug most dispensed. The results obtained in the study showed that a total of 33,068 BZD’s was dispensed, adding the first semesters of the years 2020 to 2022, the female gender showed a higher prevalence of consumption, as well as the age group that presented high consumption, was between 61 a 80 years old and the most prescribed BZD was Clonazepam.